Determination of Poisoning Cases in a Rural Tertiary Care Teaching Hospital by a Clinical Pharmacist - Ramanath , K. V.; Kumar, H. D. Naveen (Challenges and Advances in Pharmaceutical Research Vol. 7, 2022)
Background: Poison Mortality with various substances is common everywhere. Multiple agents, such as pesticides and drugs, have been used intentionally/accidentally as Poisoning in different countries. In the Indian scenario, pesticides are the most commonly used poisoning agents. Management of Poisoning is one of the biggest challenges faced by health care professionals globally. Therefore, the clinical pharmacist can play an essential role in the management/direction of Poisoning. Objective: To assess the poisoning cases admitted to the rural tertiary care hospital. Methodology: A prospective, observational study was carried out in the emergency department for nine months at Adichunchanagiri hospital and research center. Results: 73 poisoning admissions were identified during the study period. Among them, the male population is more, i.e., 63.0% compared to females 37.0%. Most victims belonged to the age group of 21-40 years. Intentional Poisoning was observed in 80.8%, followed by accidental Poisoning in 19.2%. Among the poisoning cases, pesticide exposures were observed in 57.5%, followed by bites, i.e., 13.6%, household products, 8.3%, medicine, 5.6%, and miscellaneous, 15%. The treatment assessment results showed that appropriateness with specific treatment was only 78.7%, and 21.3% specific appropriate treatment did not receive. Therapeutic outcome results showed recovered 59 (80.8%), mortality was observed in 9 (12.3%), discharge against medical advice was 4 (5.5%), and 1 (1.4%) patient was recommended for a higher center, provided Eight poison information queries management to the requestor during the study period. A poison treatment guideline was also developed/prepared to manage the poisoning cases. Conclusion: Clinical pharmacist intervention in poisoning management will reduce mortality and improve the therapeutic outcome. Most poisoning cases were observed with a pesticide that the farmers in the agriculture fields handled.